The Effect of Organizational Commitment and Work Environment on Job Satisfaction and Teachers Performance - et. al., Haerofiatna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to analyze the effect of Organizational Commitment on Job Satisfaction, the effect of Work Environment on Job Satisfaction, the influence of Organizational Commitment on Teachers Performance, the effect of Work Environment on Teachers Performance, the effect of Job Satisfaction on Teachers Performance. The analytical method used in this research is structural equation modeling (SEM) to determine the causal relationship between latent variables contained in structural equations. The analysis tool used is with the help of Smart PLS. The questionnaire was distributed electronically using simple random sampling technique. The results of the questionnaire returned were 150 respondents. Based on the results of the data analysis, it was concluded that motivation had no significant effect on Teachers Performance. Organizational Commitment has no significant effect on Job Satisfaction Performance. Work Environment has no significant effect on Job Satisfaction. Organizational Commitment affects teachers performance. Work Environment has a significant effect on teachers Performance. job satisfaction has no significant effect on teachers performance.